No regret / Intan Nurul’ain Mohd Firdaus Kozako - Mohd Firdaus Kozako, Intan Nurul’ain (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.